Role of extracellular glutamate measured by cerebral microdialysis in severe traumatic brain injury - Chamoun, Roukoz (2010)
OBJECT: Authors of several studies have implied a key role of glutamate, an excitatory amino acid, in the pathophysiology of traumatic brain injury (TBI). However, the place of glutamate measurement in clinical practice and its impact on the management of TBI has yet to be elucidated. The authors’ objective in the present study was to evaluate glutamate levels in TBI, analyzing the factors affecting them and determining their prognostic value. METHODS: A prospective study of patients with severe TBI was conducted with an inclusion criterion of a Glasgow Coma Scale score ≤ 8 within 48 hours of injury. Invasive monitoring included intracranial pressure measurements, brain tissue PO(2), jugular venous O(2) saturation, and cerebral microdialysis. Patients received standard care including mass evacuation when indicated and treatment of elevated intracranial pressure values. Demographic data, CT findings, and outcome at 6 months of follow-up were recorded. RESULTS: One hundred sixty-five patients were included in the study. Initially high glutamate values were predictive of a poor outcome. The mortality rate was 30.3% among patients with glutamate levels > 20 µmol/L, compared with 18% among those with levels ≤ 20 µmol/L. Two general patterns were recognized: Pattern 1, glutamate levels tended to normalize over the monitoring period (120 hours); and Pattern 2, glutamate levels tended to increase with time or remain abnormally elevated. Patients showing Pattern 1 had a lower mortality rate (17.1 vs 39.6%) and a better 6-month functional outcome among survivors (41.2 vs 20.7%). CONCLUSIONS: Glutamate levels measured by microdialysis appear to have an important role in TBI. Data in this study suggest that glutamate levels are correlated with the mortality rate and 6-month functional outcome.